If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25 + -7f = 8(2f + 4) Reorder the terms: -25 + -7f = 8(4 + 2f) -25 + -7f = (4 * 8 + 2f * 8) -25 + -7f = (32 + 16f) Solving -25 + -7f = 32 + 16f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-16f' to each side of the equation. -25 + -7f + -16f = 32 + 16f + -16f Combine like terms: -7f + -16f = -23f -25 + -23f = 32 + 16f + -16f Combine like terms: 16f + -16f = 0 -25 + -23f = 32 + 0 -25 + -23f = 32 Add '25' to each side of the equation. -25 + 25 + -23f = 32 + 25 Combine like terms: -25 + 25 = 0 0 + -23f = 32 + 25 -23f = 32 + 25 Combine like terms: 32 + 25 = 57 -23f = 57 Divide each side by '-23'. f = -2.47826087 Simplifying f = -2.47826087
| 3x+7=14+3x+2x | | 2x+5-4=3 | | -5(2x+1)=9 | | 2-(3x+5)=18-7x | | 3n+6=-24 | | 20x^2=-12x | | 324=-12(-6+3x) | | 3(13-6)=4(2-0.5b) | | 56+12m=60+8m | | 41/5=15-(2x+3) | | 3(4x+7)=14 | | 30-7x=10x-4 | | 6x+5=81 | | 2y-17=x | | -11(9+10a)=-1639 | | 2x-3+1=17 | | 0=x^2+13x-510 | | a^2-5a+ab-5b= | | 6x^2+8x-12=2x^2-3x+6 | | 6-a+b=4 | | 9y^2-17y+8=0 | | 16+5x=51 | | -11x^2-4x-45=0 | | 0.4w-w=0.2(3w+2) | | 14q+8r=1 | | (3x-8)=x | | 6+2d=3d-d | | 13(k-1)-3=153 | | -8(-1+7r)+10(1+3r)= | | -36+2x=-8x+x | | 9a-3b+3=6-a+b | | -6=-30-12w |